Didactics with Art: A PRISMA Systematic Review on the Integration of Flamenco in Education - Macarena Cortés-Vázquez; Carlos Chavarría-Ortiz; Diego Berraquero-Rodríguez; Jesús Heredia-Carroza (Heritage)
Flamenco, declared Intangible Cultural Heritage of Humanity by UNESCO, has aroused a growing interest as a pedagogical resource in the educational field. This systematic review analyzes its implementation in classrooms during the last decade (2014–2024), applying the PRISMA methodology to scientific articles extracted from Web of Science and Scopus. After applying inclusion and exclusion criteria using the PICOS model, 23 peer-reviewed and open-access studies were selected. The results are grouped into five thematic lines: emotional and identity development; educational and social inclusion; heritage and cultural identity; methodological and technological innovation; and experiential learning. Qualitative approaches with case studies predominate, especially in Andalusian contexts. Relevant benefits are found in terms of inclusion, emotional expression and appreciation of cultural heritage. However, limitations persist, such as the lack of systematization, scarce specific teacher training and lack of longitudinal evaluations. Flamenco thus emerges as an educational tool with high transformative potential, although its incorporation is still ad hoc and dependent on individual initiatives. It is suggested that research with mixed approaches be encouraged, that its analysis be extended to other geographical contexts and that public policies be promoted to structurally integrate flamenco into educational systems.